Determining when a fracture occurred: Does the method matter? Analysis of the similarity of three different methods for estimating time since fracture of juvenile long bones. (January 2018) - Drury, Anne; Cunningham, Craig
Abstract: Radiographic fracture date estimation is a critical component of skeletal trauma analysis in the living. Several timetables have been proposed for how the appearance of radiographic features can be interpreted to provide a likely time frame for fracture occurrence. This study compares three such timetables for pediatric fractures, by Islam et al. (2000), Malone et al. (2011), and Prosser et al. (2012), in order to determine whether the fracture date ranges produced by using these methods are in agreement with one another. Fracture date ranges were estimated for 112 long bone fractures in 96 children aged 1–17 years, using the three different timetables. The extent of similarity of the intervals was tested by statistically comparing the overlap between the ranges. Results showed that none of the methods were in perfect agreement with one another. Differences seen included the size of the estimated date range for when a fracture occurred, and the specific dates given for both the upper and lower ends of the fracture date range. There was greater similarity between the ranges produced by Malone et al. (2011) and both the other two studies than there was between Islam et al. (2000) and Prosser et al. (2012). The greatest similarity existed between Malone et al. (2011) and Islam et al. (2000). The extent of differences between methods can vary widely, depending on the fracture analysed. Using one timetable gives an average earliest possible fracture date of less than 2 days before another, but the range was extreme, with one method estimating minimum time since fracture as 25 days before another method for a given fracture. In most cases, one method gave maximum time since fracture as a week less than the other two methods, but range was extreme and some estimates were nearly two months different. The variability in fracture date estimates given by these timetables indicates that caution should be exercised when estimating the timing of a juvenile fracture if relying solely on one of the published guides. Future research should be undertaken to compare these methods on a population of known fracture timing, and to better understand the relationship between age of the individual, skeletal health, fracture healing rates, and radiographic characteristics of fracture healing. Highlights: There are three primary existing radiographic fracture healing timelines for juveniles. Timetables disagree by margins varying from days to months depending on age of the fracture. Caution should be exercised when estimating time since fracture in a pediatric case. Research should be repeated on a population of known fracture dates. Future research should include testing of inter-observer error.